O uso do Target Costing por montadoras de veículos automotores com fábricas no Brasil - Silva, Gilmar Pego da (2014)
The System Cost Management Target Costing" was developed by the Japanese in the sixties from the technique developed in the United States called Value Engineering, that emerged after World War II due the shortage of raw materials. The "Target Costing" consists in extract the cost from the selling price determined by the market where it s given the maximum allowable cost to reach a desired result (interest). Its application becomes vital as bigger the competitive market and its origins becomes. Even being relatively new (definetivelly has arrived at occident by the 80 s decade and became known by near 2000 s at Brasil) the system was quickly adapted to the local culture, but even so it kept the japanese s fundamentals. The study is hampered because there wasn t any academic connection, what makes the national literature very rare and the same occur to the understanding of cultural factors that induced the adaptations noted in its application. This academic article aimed to collect data and meet through a research that used of descriptive and exploratory method to identify whether the automotive segment automakers affiliated automotive vehicles ANFAVEA (National Association of Automotive Vehicle Makers) use the system management costs "target costing". After tabulating the answers was possible to find out that this kind of industry use, in essence, the system management costs "target costing" and that some adjustments have happened, such as the use of it for new products and also in existing products, focusing the decrease of costs and increasing the profits, even if in some situations the companies accept higher prices than the allowable costs once it has a premise of action to reduce future costs and improve the results. Target costing application in other products act besides direct costs, variable costs, logistic costs and depreciation basis for these costs